Nonactivated thromboelastometry able to detect fibrinolysis in contrast to activated methods (EXTEM, INTEM) in a bleeding patient. Issue 7 (October 2016) - Durila, Miroslav
Abstract : Rotational thromboelastometry (ROTEM) is increasingly used in practice to monitor coagulation status of severely bleeding patients and it helps to provide aimed therapy. The main advantage of ROTEM is detection of fibrinolysis. To get fast results, the reagents for activation, either extrinsic or intrinsic pathway of coagulation, are used. Although this method gives information about whole blood coagulation, in some cases, the patient is bleeding despite normal values of ROTEM. We present a case of a bleeding patient with normal values of activated ROTEM method (EXTEM, INTEM). However, nonactivated method (NATEM) was able to detect fibrinolysis and no clot was found in the cuvette. When tranexamic acid was added to the cuvette, the trace came back to normal value and a clot was formed inside the cuvette. According to this finding, the patient was effectively treated with antifibrinolytic drugs and stopped bleeding. In this case, we want to demonstrate that NATEM, as nonactivated ROTEM, seems to be more sensitive to coagulation changes, especially in detection of fibrinolysis, than activated ROTEM methods.